Positive and Negative Regulation of Cellular Immune Responses in Physiologic Conditions and Diseases. (26th March 2012) - Viganò, S.; Perreau, M.; Pantaleo, G.; Harari, A.
Abstract : The immune system has evolved to allow robust responses against pathogens while avoiding autoimmunity. This is notably enabled by stimulatory and inhibitory signals which contribute to the regulation of immune responses. In the presence of a pathogen, a specific and effective immune response must be induced and this leads to antigen-specific T-cell proliferation, cytokines production, and induction of T-cell differentiation toward an effector phenotype. After clearance or control of the pathogen, the effector immune response must be terminated in order to avoid tissue damage and chronic inflammation and this process involves coinhibitory molecules. When the immune system fails to eliminate or control the pathogen, continuous stimulation of T cells prevents the full contraction and leads to the functional exhaustion of effector T cells. Several evidences both in vitro and in vivo suggest that this anergic state can be reverted by blocking the interactions between coinhibitory molecules and their ligands. The potential to revert exhausted or inactivated T-cell responses following selective blocking of their function made these markers interesting targets for therapeutic interventions in patients with persistent viral infections or cancer.